Analysis of moral repressive actions through the implementation of local customary norms: 'Cuci Kampung' in Bengkulu City - Susanti, Atika (Institute of Computer Science (IOCS), 2024)
This study aims to describe the moral repressive actions occurring through the implementation of Local Customary Norms and Traditions, particularly in the practice of 'Cuci Kampung' in Bengkulu City. The research seeks to comprehend how customary norms and local traditions lead to moral repressive actions within the local community. Employing a qualitative descriptive research method involving data collection through in-depth interviews with relevant parties, participatory observations, and documentation analysis of narratives depicting the execution of 'Cuci Kampung' and its impact on individuals and communities. Subsequently, the data was cross-checked to ensure accuracy. Data sources included local customary leaders and religious figures in the Pondok Besi neighborhood. Analysis was conducted using the Miles and Huberman approach, involving data reduction, data presentation, and conclusion drawing. The result of this research is an analysis of the relationship between local traditions, the customary norms of 'cuci kampung,' and moral repressive actions. The study discovered that the implementation of Local Customary Norms and Traditions, such as in the practice of 'Cuci Kampung,' could become a powerful mechanism for social control. However, it often imposes moral pressure on individuals not entirely in line with the existing norms, resulting in internal and external conflicts.